2000
DOI: 10.1097/00001756-200011270-00018
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic A10 dopamine neurones in a rat model of attention-deficit hyperactivity disorder (ADHD)

Abstract: To clarify whether a hypo or hyperfunctioning mesocorticolimbic system is the neural substrate of Attention-Deficit Hyperactivity Disorder (ADHD), we carried out a morphometric analysis on an animal model, the Naples high excitability rat (NHE). Male adult NHE and control rats were used for tyrosine hydroxylase (TH) immunocytochemistry in the ventral tegmental area and substantia nigra in coronal cryostat sections. PC-assisted image analysis showed larger DA neurones in the ventral tegmental area but not in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Furthermore, the cellular and molecular mechanisms that underlie the increased dopaminergic activity in these mice also remain unknown. Previous studies have shown that changes in dopamine neuronal size are associated with differences in reward-related behavior, depression-related behavior, and hyperactivity (Krishnan et al, 2008a;Russo et al, 2007;Viggiano and Sadile, 2000). Here we find that changes in dopamine cell morphology and neuronal activity are important for the expression of hyperactivity and anxiety-related phenotypes of the ClockD19 mice, and that chronic lithium likely restores proper behavior in part through the modulation of this system.…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, the cellular and molecular mechanisms that underlie the increased dopaminergic activity in these mice also remain unknown. Previous studies have shown that changes in dopamine neuronal size are associated with differences in reward-related behavior, depression-related behavior, and hyperactivity (Krishnan et al, 2008a;Russo et al, 2007;Viggiano and Sadile, 2000). Here we find that changes in dopamine cell morphology and neuronal activity are important for the expression of hyperactivity and anxiety-related phenotypes of the ClockD19 mice, and that chronic lithium likely restores proper behavior in part through the modulation of this system.…”
Section: Introductionsupporting
confidence: 64%
“…This view is supported by the increase in TH activity found in another animal model of ADHD, the Naples highexcitability (NHE) rat (Viggiano et al, 2000(Viggiano et al, , 2002. If one assumes that the SHR phenotype is a model of ADHD, then the higher dopamine basal concentration found in the NAc of SHR as compared with WKY rats (Carboni et (Kumai et al, 1996) and TH gene expression (Reja et al, 2002) in the medulla oblongata of SHR rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tyrosine hydroxylase, DAT and D 2 receptor mRNA are hyperexpressed in the PFC, while the D 1 receptor is down-regulated. No such changes have been reported for the striatum (Viggiano et al 2002a(Viggiano et al , b, 2003aViggiano and Sadile 2000).…”
Section: The Coloboma Mutant Mousementioning
confidence: 94%